Ultrasensitive sandwich RNA-aptasensor based on dual-signal amplification strategy for highly sensitive neomycin detection. (January 2022) - Li, Falan; Gao, Xiaolin; Wang, Xiaoyang; Guo, Yemin; Sun, Xia; Yang, Qingqing; Zhang, Yanyan
Abstract: This study aimed to design a highly sensitive electrochemical aptasensor based on the dual-signal amplification strategy for detecting neomycin (NEO) in milk samples. The electronic signal of multi-walled carbon nanotubes (MWCNTs) was greatly improved due to the existence of ferrocene (Fc), which had good electron transfer ability. The silica hybridized mesoporous ferroferric oxide nanoparticles (Fe3 O4 @SiO2 ) were prepared by hydrothermal and chemical activation treatments, which had a large specific pore volume and a large specific surface area, they could fix more RNA aptamers (Apts) and promote the electron transfer of nanoparticle labels. A composite sandwich was formed between the two Apts (Apt1 and Apt2) and the target. Also, Apt2 was modified by gold nanoparticles (AuNPs), enhancing the electrochemical signal. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used to characterize the performance of the aptasensor in detail. Under optimized conditions, the response current differences of the electrochemical aptasensor exhibited a linear relationship toward the positive logarithm of NEO concentrations ranging from 5 × 10 −3 nM to 5 × 10 2 nM and a detection limit of 0.759 nM. The electrochemical aptasensor showed specificity and selectivity. In addition, the constructed aptasensor was successfully applied to the detection of NEO in milk. These results indicated that the aptasensor had potential applications in the actual monitoring of NEO. Highlights: An electrochemical aptasensor was constructed with a dual-signal amplification strategy. Two RNA Apts were used to better fix the NEO in the middle to form a sandwich structure. By constructing Fc-MWCNTs and Fe3O4@SiO2, the storage stability was improved. This aptasensor shows good analytical performance in neomycin.